Preventing fraud victimisation against older adults: towards a holistic model for protection - Button, Mark (International journal of law, crime and justice, 2024)
The prevention of fraud against older adults and other age groups, has been the subject of limited research with very few systematic attempts to map different tools and strategies that are used. This paper using the UK and South Korea as a starting point, but other countries too, maps some of the most common tools and strategies used to prevent frauds that target older adults. It develops the first comprehensive typology of strategies built upon the degree to which they embrace modern technology. It shows much of the prevention used is low tech, but high-tech solutions rooted in the fourth industrial revolution technologies are emerging and growing. The paper draws these different strategies and tools together to offer a holistic model for the prevention of fraud against older adults for further debate and utilisation by professionals.